Content analysis of Pancasila and Civic Education curriculum at the junior high school level in Indonesia: Philosophical perspectives in affirming civic identity - Sunarso, Sunarso; Hidayah, Yayuk; Firmasnyah, Akmal; Arpannudin, Iqbal (Universitas Negeri Yogyakarta, 2024)
This article examines the Pancasila and Civic education curriculum at the Junior High School level in Indonesia using a philosophical approach. It analyzes the curriculum's goals, values, and principles to affirm students' civic identity. The study uses a literature analysis of scientific journals, articles, books, research reports, news, and government policies. Findings include the success of curriculum implementation, areas for improvement, and differences in approaches across schools. The authors compare teaching strategies and assessment approaches using a philosophical perspective. The quality of sources is evaluated for reliability, accuracy, objectivity, and relevance. The article recommends future research to strengthen students' understanding and appreciation of Pancasila values and affirm their Indonesian citizenship identity.